Feasibility of manufacture and investigation of physicochemical properties of camel milk – based ice cream - Jafarpour, Afshin (Journal of Scientific Agriculture, 2017)
Ice cream is one of the most popular foods worldwide commonly made from cow milk. Camel milk is an invaluable foods component which is less frequently used in diets. The aim of this study was to provide a proper formulation for manufacture of ice cream using camel milk and investigate the physicochemical and organoleptic properties of camel milk – made ice cream. The results showed no significant difference between fat and protein contents however solid matters content viscosity and melting point of cow milk containing sample were higher than those of camel milk containing ice cream. Sensory tests also did not show any significant difference among samples. Thus manufacture and competition of an ice cream made from camel milk is feasible.